Sintese e avaliação de peptidomiméticos contendo heterociclos de três membros como inibidores de catepsina L - Santos, Deborah Araujo dos (2017)
Cathepsin L is a lysosomal cysteine protease, that is related to many physiological processes, however overexpression and up- or downregulation may cause several pathologies. Therefore, cathepsin L became an interesting drug target. Peptidyl epoxides and aziridines are reported as potent cathepsin inhibitors.Previously, our research group has synthesized six new epoxi-α-acyloxycarboxamides through one-pot process starting with an organocatalyzed asymmetric epoxidation using catalyst I followed by Passerini reaction. Then, inhibitory assays against cathepsins K, L and V were performed, and the new compounds presented inhibition, mainly against cathepsin L. In order to further evaluate the structure-activity relationship of epoxi-α-acyloxycarboxamides 11 new compounds were synthesized. Among all, LPSN423 exhibited the best inhibitory activity. The mechanistic study showed that LSPN423 is a reversible tight binding uncompetitive inhibitor, which characterized by a high affinity enzyme-inhibitor complex. To further explore the application of 2,3-epoxi-aldehydes in multicomponent reactions, in addition to create a library of compounds to be evaluated against cathepsin L, Ugi reaction were performed sequentially to epoxidation. The 2-step procedure furnished the desired product with yields ranged from 22% to 68%. The new epoxi-α-acylaminocarboxamides were tested against cathepsin L and no significant activity was observed. The organocatalytic aziridination reaction is reported, however some drawbacks are associated with this reaction, such as the use of chlorinated solvents and large excess of base to promote the reaction. Thus, catalyst I allowed the use of the greener solvent mixture ethanol/water and a lower amount of base. Another drawback of this reaction is the unstable product, so to overcome this issue, the one-pot Passerini reaction was performed, right after the completion of the aziridination; the desired products were obtained from moderate to good yields. Preliminary evaluation of the new aziridine peptidomimetics indicates a potential activity of this class of compounds, although further studies are required.